Changes in post-event processing during cognitive behavioural therapy for social anxiety disorder: A longitudinal analysis using post-session measurement and experience sampling methodology. (August 2019) - Katz, Danielle E.; Cassin, Stephanie; Weerasinghe, Rashmi; Rector, Neil A.
Highlights: Momentary post-event processing decreased during cognitive behavioural therapy. Dispositional measurements of post-event processing decreased during treatment. Decreases in momentary and dispositional post-event processing predicted outcome. Abstract: Purpose: Post-event processing (PEP) is posited to be an important factor in the maintenance of social anxiety symptoms. Previous research has demonstrated that general PEP tendencies are sensitive to treatment. However, it remains unclear how momentary PEP following social interactions changes over the course of treatment for social anxiety disorder. The purpose of the present study was to examine how both momentary and general PEP change over the course of treatment, and how such changes predict treatment outcome. Method: Participants (N = 60) with social anxiety disorder were enrolled in group cognitive behavioural therapy. All participants completed measures of PEP and social anxiety symptom severity at five time points over treatment. A subset (N = 33) also completed repeated experience sampling measurements of PEP following social interactions across the course of treatment. Results: Both general and momentary PEP decreased over the course of treatment. Decreases in both types of PEP predicted lower social anxiety symptom severity following treatment. Conclusion: The results of the study demonstrate that momentary experiences of PEP can be influenced by treatment, and can in turn impact treatment outcome. The findings have significant clinical and theoretical implications.